2008
DOI: 10.1097/tp.0b013e31816349b5
|View full text |Cite
|
Sign up to set email alerts
|

HLA Mismatches Remain Risk Factors for Acute Kidney Allograft Rejection in Patients Receiving Quadruple Immunosuppression With Anti-Interleukin-2 Receptor Antibodies

Abstract: Although infrequent in patients receiving modern immunosuppressive drugs, acute rejection remains an important risk factor for graft loss after renal transplantation. Our results suggest that better HLA matching and shorter periods of dialysis before transplantation could reduce acute rejection rates and further improve outcomes under current immunosuppressive regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 35 publications
3
30
0
Order By: Relevance
“…Although this is much higher than the 10 to 15% rejection incidence reported with a comparable quadruple immunosuppressive regimen in low-risk patients, 1,16 it is similar to recent data from other studies involving HLA-sensitized patients. [7][8][9][10] Our study was not powered to reveal significant differences in graft survival between the ATG and daclizumab arms, but post hoc analysis of the total patient population revealed that, when compared with patients who remained rejection-free, both graft function and graft survival were significantly lower among patients who experienced rejection.…”
Section: Discussionmentioning
confidence: 36%
See 1 more Smart Citation
“…Although this is much higher than the 10 to 15% rejection incidence reported with a comparable quadruple immunosuppressive regimen in low-risk patients, 1,16 it is similar to recent data from other studies involving HLA-sensitized patients. [7][8][9][10] Our study was not powered to reveal significant differences in graft survival between the ATG and daclizumab arms, but post hoc analysis of the total patient population revealed that, when compared with patients who remained rejection-free, both graft function and graft survival were significantly lower among patients who experienced rejection.…”
Section: Discussionmentioning
confidence: 36%
“…Moreover, despite the availability of potent immunosuppressive drugs such as tacrolimus and mycophenolate mofetil (MMF), the negative impact of AR episodes on graft survival has remained important. 1 Acute rejection typically occurs during the first weeks after transplantation, and consequently, to suppress lymphocyte func-tion, many kidney transplant recipients receive induction therapy with either lymphocyte-depleting rabbit antithymocyte globulin (ATG) or nondepleting IL-2 receptor-antagonizing monoclonal antibodies (IL2RA mAbs). 2 Both types of anti-lymphocytes are equally effective in lowrisk recipients (i.e., patients with no previous exposure to HLA antigens).…”
mentioning
confidence: 99%
“…Matching at the HLA-ABDR loci remains the cornerstone of deceased donor kidney allocation in Australia and worldwide because of the association between incremental HLA-ABDR mismatches and increased risk of rejection and/or graft loss after kidney transplantation (1)(2)(3). Although differences in HLA-DQ matching between donors and recipients have been shown to be associated with adverse graft outcomes, matching at the HLA-DQ locus is not explicitly considered in the allocation algorithm for deceased donor kidney transplantation (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…[11] Basiliximab binds specifically and with high affinity to IL-2Ra (dissociation constant [K D ] of 0.1 nmol L) on antigen-activated T lymphocytes and competitively inhibits IL-2 binding to the receptor, thereby inhibiting IL-2-mediated proliferation of T lymphocytes, a critical step in the cellular immune response involved in allograft rejection. [8,9] The specific epitope on IL-2Ra to which basiliximab binds is the seven amino acid string E-R-I-Y-H-F-V at positions [116][117][118][119][120][121][122] in the extracellular domain of the a-chain, which includes three of the IL-2 contact sites at amino acids I-Y-H (positions 118-120). [8,9] The specific epitope on IL-2Ra to which basiliximab binds is the seven amino acid string E-R-I-Y-H-F-V at positions [116][117][118][119][120][121][122] in the extracellular domain of the a-chain, which includes three of the IL-2 contact sites at amino acids I-Y-H (positions 118-120).…”
Section: Pharmacodynamic Propertiesmentioning
confidence: 99%